A Rare Case of Cholestasis: Arthrogryposis, Renal Tubular Disorder and Cholestasis Syndrome - Yelda Türkmenoğlu; Yeşim Acar; Fatih Cemal Özdemir; Ralfi Singer; Afig Berdeli; Servet Erdal Adal (Galenos Yayinevi, 2018)
Arthrogryposis, renal tubular dysfunction and cholestasis (ARC) syndrome is a rare, autosomal recessive multisystem disorder. Severe growth retardation, ichthyosis, recurrent febrile disease, platelet abnormalities, sensorineural hearing loss, hypotonia and corpus callosum dysgenesis were later included as further features of this syndrome. We present a case of ARC syndrome diagnosed by genetic analysis.